Drama as a Tool of Social Conflict Management: “Jalan Asmaradana” Performance Project - Nurhasanah, Een; Hussin, Hanafi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
This study examines the process of the drama staging project